Case Study : Rightontrack Sdn Bhd / Muhammad Aiman Ab Manaf - Ab Manaf, Muhammad Aiman (2020)
Rightontrack Sdn Bhd is a company based in Kelana Jaya, Selangor, prioritized on fleet management and vehicle tracking. With more than ten years of experience, Rightontrack has strengthened its place as one of the top companies in Malaysia offering web-based vehicle tracking solution. The company is a MSC Status Company, which is a recognition by the Government of Malaysia through the Multimedia Development Corporation (MDeC) and is proudly 100% Malaysian owned.